Strategi Coping Stres pada Remaja dalam Hubungan Pacaran yang Sehat Stress Coping Strategies in Adolescents within Healthy Dating - Michael Tandya; Evy Tjahjono (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Dating violence can manifest in various forms, including silent treatment, threats of breakup, physical violence, and demeaning behaviour, which negatively impact the emotional and physical well-being of victims. Conflicts in relationships are often triggered by jealousy, excessive control, and disagreements, which undermine trust and create an unhealthy environment. Psychological violence such as silent treatment and threats of breakup causes deep emotional stress, while physical violence like hitting has direct effects on the victim's body.Individuals use coping strategies to manage stress in relationships, with approaches including emotion-focused coping, such as apologising and maintaining distance, and problem-focused coping, such as self-care and open communication. Understanding what constitutes a healthy relationship is crucial, encompassing two-way communication, openness, commitment, and respect for personal boundaries to create a safe and respectful relationship.Support from social and family environments plays a crucial role in helping victims endure abusive relationships. Emotional support, constructive advice, and encouragement to seek professional help can reduce stress and improve emotional well-being, and are key factors in the recovery process for victims.